Pengaruh Curah Hujan Dan Hari Hujan Terhadap Produksi Kelapa Sawit Berumur 7, 10, Dan 13 Tahun Di Kebun Huta Padang PT. Perkebunan Nusantara III Persero - Tengku Sofi Hans Hamdan; Irsal Irsal; Lisa Mawarni (Jurnal Agroekoteknologi, 2018)
ABSTRACT   Palm oil production depend on the rain and the age composition of plants. The purpose of this research was to determine the effect of rainfall and rainy day as well as the correlation of both on palm oil production in plants aged 7, 10 and 13 years. This research used primary data available in company administration, in the form data of production of fresh fruit bunches (FFB); componen production data as total bunches, average bunches weight, and total of productive trees in 2013, 2014,2015.  Rainfall and rainy days data were taken a year before the production data in 2012, 2013, 2014. Analysis method used are double linier regression and correlation analysis. Model tested by classic asumption consists of normality test, heteroskedasticity test, multicollinearity, and autocorellations test by using statistic software SPSS.v.20 for windows. The result of t-partial test showed that rainfall variable had an effect not significantly on age 7, 10 and 13 years at alpha 5% (Sig > α 0.05). While on rainy day variable showed that rainy day had significant effect at age 7 year at alpha 5% (Sig < α 0.05)  while at age 10 and 13 year rainy day had an effect not real. While on the regression analysis shows that rain fall and rainy day simultaneously variables unsignificanted with  alpha 5% (Sig <α 0.05) to increase the production of FFB at the age of 7, and 10 years. While rain fall and rainy day variables significanted to increase the production of FFB at the age of 13 years. The influence of rainfall and rainy days the FFB production each from ages 7, 10 and 13 years  was 50,4%, 44,7%, and 43,8% influence by other variables not included on the model. Correlation results in plants was 7, 10, and 13 years with two-way analysis test at 1% level showed variable rainfall and rainy days have a strong relationship, and positive direction. Keywords: FFB production, rainfall, rainy day.